Self-talk on sport performance and selected psychological variables: a systematic review / Mohd Saufi Dali, Mohad Anizu Mohd Nor and Ahmad Fikri Mohd Kassim - Dali, Mohd Saufi; Mohd Nor, Mohad Anizu; Mohd Kassim, Ahmad Fikri (Universiti Teknologi MARA, 2023)
Self-talk is a psychological skill training that improves motor performance and sports skills among athletes. Previous research has indicated differences between motivational self-talk and instructional self-talk in sports performance. However, there is a lack of attention paid to the effectiveness of self-talk toward psychological barriers. Therefore, the primary aim of this study was to examine past studies on the effect of self-talk on sports performance and to select psychological variables among athletes. Through a systematic review, we analysed the scientific production concerning the sports psychology of self-talk toward athletes. The process review was conducted by the PRISMA protocol and a search performed by using online data sources (Scopus, Web of Science, and Semantic Scholar), as well as, conference proceedings of possibly related papers. The search was limited to articles published within ten years and written in English. A total of 38 studies were analysed. Referring to a total of 38 studies (nine articles focused on the self-talk questionnaire, six articles on motivational self-talk, six articles on instructional studies, and 17 articles focused on both motivational self-talk). Based on this, only 9 studies satisfied the eligibility criteria related to sports performance and psychological effects. As a result, a sample of 9 studies was subjected to systematic quality analysis. The analysis results showed that negative self-talk decreases athletes' performance. In addition, there is inconsistent evidence on the effect of motivational and instructional self-talk based on specific sports. Based on this review, instructional self-talk is beneficial for fine skills (freethrow basketball and penalty shoot-out), and motivational self-talk is effective for gross skill (running). Thus, it can be concluded that both motivational and instructional self-talk play an important role in enhancing motor performance.